Just double the angle

Calculus Level 3

( j = 0 ( 1 ) j x 2 j ( 2 j ) ! ) ( k = 0 ( 1 ) k x 2 k + 1 ( 2 k + 1 ) ! ) \large \left( \sum_{j=0}^\infty \dfrac{(-1)^{j} x^{2j}}{(2j)!} \right) \left( \sum_{k=0}^\infty \dfrac{(-1)^{k} x^{2k+1}}{(2k+1)!} \right)

Which of the following must be equal to the expression above?

q = 0 ( 1 ) q ( 2 x ) 2 q 2 ( 2 q ) ! \sum_{q=0}^\infty \dfrac{(-1)^{q} (2x)^{2q}}{2(2q)!} s = 0 ( 1 ) s + 1 ( 2 x ) 2 s 2 ( 2 s ) ! \sum_{s=0}^\infty \dfrac{(-1)^{s+1} (2x)^{2s}}{2(2s)!} p = 0 ( 1 ) p ( 2 x ) 2 p + 1 2 ( 2 p + 1 ) ! \sum_{p=0}^\infty \dfrac{(-1)^{p} (2x)^{2p+1}}{2(2p+1)!} r = 0 ( 1 ) r + 1 ( 2 x ) 2 r + 1 2 ( 2 r + 1 ) ! \sum_{r=0}^\infty \dfrac{(-1)^{r+1} (2x)^{2r+1}}{2(2r+1)!}

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Michael Mendrin
Aug 15, 2016

The title gives away the solution. We're looking at the series expansion of

C o s ( x ) S i n ( x ) = 1 2 S i n ( 2 x ) Cos(x)Sin(x)=\dfrac{1}{2}Sin(2x)

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...